ANALISIS PEWARNA RHODAMIN B DALAM SAUS TOMAT YANG BEREDAR DI KOTA MAKASSAR SECARA SPEKTROFOTOMETRI UV-VIS - St. Maryam; A. Muflihunna; Ulfa Sajadah (As-Syifaa Jurnal Farmasi, 2014)
Analysis of Rhodamin B dye have done in several tomato sauce produced of Makassar city. The research aims to define and analyze levels of compound Rhodamin B in tomato sauce produced Makassar which is source from the sidewalk traders, and industries households by Thin Layer Chromatography (TLC) method for qualitative analysis and spectrophotometry UV-Vis for quantitative analysis. This research can provide benefits to the public about dangers of consuming food that contain of Rhodamin B dye. Extraction with wool yarn, identified by TLC, and analysis by spectrophotometry UV Vis were covered in this study. Research results showed that the four of tomato sauce produced in makassar city did not contain of Rhodamin B dye and that product can be used by the citizen.Key Words : Rhodamin B, Spectrophotometry UV-Vis, Tomato Sauce.